QRT-PCR versus IFA-based Quantification of Male and Female Gametocytes in Low-Density Plasmodium falciparum Infections and Their Relevance for Transmission. (22nd August 2019) - Gruenberg, Maria; Hofmann, Natalie E; Nate, Elma; Karl, Stephan; Robinson, Leanne J; Lanke, Kjerstin; Smith, Thomas A; Bousema, Teun; Felger, Ingrid
Abstract: Background: Accurate quantification of female and male gametocytes and sex ratios in asymptomatic low-density malaria infections are important for assessing their transmission potential. Gametocytes often escape detection even by molecular methods, therefore ultralow gametocyte densities were quantified in large blood volumes. Methods: Female and male gametocytes were quantified in 161 PCR-positive Plasmodium falciparum infections from a cross-sectional survey in Papua New Guinea. Ten-fold concentrated RNA from 800 µL blood was analyzed using female-specific pfs25 and male-specific pfmget or mssp qRT-PCR. Gametocyte sex ratios from qRT-PCR were compared with those from immunofluorescence assays (IFA). Results: Gametocytes were identified in 58% (93/161) P. falciparum -positive individuals. Mean gametocyte densities were frequently below 1 female and 1 male gametocyte/µL by qRT-PCR. The mean proportion of males was 0.39 (95% confidence interval, 0.33–0.44) by pfs25 / pfmget qRT-PCR; this correlated well with IFA results (Pearsons r 2 = 0.91; P < .001). A Poisson model fitted to our data predicted 16% P. falciparum -positive individuals that are likely to transmit, assuming at least 1 female and 1 male gametocyte per 2.5 µL mosquito bloodmeal. Conclusions: Based on model estimates of female and male gametocytes per 2.5 µL blood, P. falciparum -positive individuals detected exclusively by ultrasensitive diagnostics are negligible for human-to-mosquito transmission. Estimating the transmission potential of ultralow-density malaria infections informs interventions. Almost all infections with ≥1 female and male gametocyte per 2.5 µL mosquito bloodmeal, and thus with highest likelihood of contributing to human-to-mosquito transmission, were detectable by standard molecular diagnostics.